Analisis Implementasi Program Sabtu Budaya Di Sekolah Dasar Kota Mataram Terhadap Literasi Budaya Peserta Didik - Muhammad Tahir; muhammad Sobri; Setiani Novitasari; Asri Fauzi (Journal on Education, 2024)
This research aims to examine and analyze the extent to which the implementation of the Cultural Saturday Program in Mataram City Elementary Schools has affected students' cultural literacy. This research includes qualitative research with descriptive research type. Data collection in this research used observation, questionnaires and documentation. The data that has been collected is analyzed through three stages, including: reduction, data presentation/data display, and conclusion verification. The research results concluded that; 1) there are several activities that have been implemented by elementary schools in Mataram City in the Cultural Saturday program, namely: a) conversations using regional languages; b) get to know traditional foods and snacks; c) Sasak language fairy tales; d) Wearing traditional Sasak clothes; e) introduce traditional games; f) performing traditional dances; g) begibung (eating together). 2) The cultural literacy of students in Mataram city elementary schools is in the good category. Based on the results of data analysis, it can be seen that on average from 13 elementary schools in the city of Mataram, an average score of 33 was obtained with a percentage of 75%.